Achieving the 4IR University Library in Sub-Saharan Africa: Trends, Opportunities and Challenges - Nkiko, Christopher; Okuonghae, Omorodion (Folia Toruniensia, 2021)
Aim: The paper examined the university library in the Fourth Industrial Revolution (4IR) and the preconditions for achieving and sustaining the same in Nigeria. 4IR is characterized by a level of automation, deployment of emerging technologies and artificial intelligence, internet connectivity and accessibility to the global information network, subscription to reputable online databases, quality and comprehensive collection in diverse formats, preponderance of digital natives among patrons, increased demand for seamless access to online resources and virtual operations, new library spaces (learning commons, research commons and makerspace), open scholarly communication, research data management, social mediation applications, digital curation and preservation. The challenges militating against effective crystallization of 4IR university libraries include: financial constraints, inadequate infrastructure, resistance to change, inadequate skills and competencies, security and intrusion issues, lack of exposure to international standards. Conclusions: The paper recommended the following as requisite panacea: leadership, demonstrating and justifying returns on investment, benchmarking practices, anti-intrusion and back-up systems, adequate power supply and bandwidth, endowment and corporate social responsibility, indigenous library management software, and capacity building initiatives.